Zastosowanie plastrowania dynamicznego u chorych wieku podeszłym po leczeniu operacyjnym stenozy zwyrodnieniowej kanału kręgowego i dyskopatii lędźwiowej = The application of Kinesio Taping in eldery patients after surgical treatment of lumbar spinal stenosis and disc herniation - Główczewska-Siedlecka, Emilia; Mądra-Gackowska, Katarzyna; Nowacka, Krystyna; Simińska, Joanna; Siedlecki, Zygmunt; Szostak, Mateusz; Kędziora Kornatowska, Kornelia (Journal of Education, Health and Sport, 2016)
Główczewska-Siedlecka Emilia, Mądra-Gackowska Katarzyna, Nowacka Krystyna, Simińska Joanna, Siedlecki Zygmunt, Szostak Mateusz, Kędziora-Kornatowska Kornelia. Zastosowanie plastrowania dynamicznego u chorych wieku podeszłym po leczeniu operacyjnym stenozy zwyrodnieniowej kanału kręgowego i dyskopatii lędźwiowej = The application of Kinesio Taping in eldery patients after surgical treatment of lumbar spinal stenosis and disc herniation. Journal of Education, Health and Sport. 2016;6(12):222-229. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.197908 http://ojs.ukw.edu.pl/index.php/johs/article/view/4051 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.11.2016. Revised 28.11.2016. Accepted: 09.12.2016. Zastosowanie plastrowania dynamicznego u chorych wieku podeszłym po leczeniu operacyjnym stenozy zwyrodnieniowej kanału kręgowego i dyskopatii lędźwiowej The application of Kinesio Taping in eldery patients after surgical treatment of lumbar spinal stenosis and disc herniation Główczewska-Siedlecka Emilia1, Mądra-Gackowska Katarzyna1, Nowacka Krystyna2, Simińska Joanna2, Siedlecki Zygmunt3, Szostak Mateusz3, Kędziora‑Kornatowska Kornelia1 1. Katedra i Klinika Geriatrii, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Katedra i Klinika Rehabilitacji, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 3. Klinika Neurochirurgii, Neurotraumatologii i Neurochiurgii Dziecięcej, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Streszczenie Plastrowanie dynamiczne (ang. Kinesio Taping) jest coraz bardziej popularną metodą leczenia zespołów bólowych mięśniowo - szkieletowych oraz kręgosłupa. Może być to pojedyncza metoda leczenia zachowawczego oraz wspomaganie innych. Plastrowanie można stosować jako uzupełnienie kinezyterapii, terapii manualnej oraz po zabiegach neurochirurgicznych kręgosłupa, jako uzupełnienie postępowania pooperacyjnego. Niniejsza praca przedstawia wyniki plastrowania chorych w wieku podeszłym po operacjach z obrębie kręgosłupa lędźwiowego. Pacjentom w grupie badanej naklejono plastry Kinesio Taping w pierwszej dobie po zabiegu. Uzyskano zmniejszenie bólu po zabiegu operacyjnym w grupie stosującej plastrowanie dynamiczne. W grupie kontrolnej dolegliwości bólowe po zabiegu były większe niż w grupie badanej, co dowodzi że Kinesio Taping może być stosowany z powodzeniem u chorych w wieku podeszłym po leczeniu operacyjnym w obrębie kręgosłupa lędźwiowego. Słowa kluczowe: Kinesio Taping, geriatria, dyskopatia lędźwiowa, stenoza zwyrodnieniowa, zespoły bólowe kręgosłupa Abstract Kinesio Taping is popular method of treating musculo - skeletal pain and low back pain. This can be a single method of conservative treatment or can support other methods like physiotherapy, manual therapy or after neurosurgical spine procedures. The study presents results of Kinesio Taping in eldery, geriatric patients after surgical treatment of lumbar spine comparing to eldery patients after neurosurgical procedures without Kinesio Taping. Patients in the study group had applied Kinesio Taping the first day post op. The pain relief after surgery in the group using Kinesio Taping was observed. In the control group pain after surgery they were greater than those in the study group, which proves that Kinesio Taping can be used successfully in eldery patients after surgery of lumbar spine. Key words: Kinesio Taping, geriatrics, lumbar discopathy, lumbar spinal stenosis, low back pain